Implementasi Lean Warehouse terhadap Produktivitas Operasional Pengiriman di PT. ABC - Fadila Ainur Rahma; Ma’ruf Ma’ruf; Wenny Ananda Larasati (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the level of lean warehouse implementation and the dominant aspects that can affect the productivity of shipping operations at PT. ABC. The approach adopted in this study is quantitative descriptive by distributing questionnaires to respondents involved in shipping operations both in administration and in the field. The results obtained that the level of lean warehouse implementation reached 55.17%, which indicates that most lean warehouse aspects have been implemented but are not optimal in some aspects. The dimensions of motion, waiting, overprocessing, transportation, and flow management are still in the